Evaluation of field performance of prefabricated vertical drains (PVD) for soil ground improvement in the southern vietnam - Tran-Nguyen, Hoang-Hung.; HO, Huong L.T.; Ha, Hy. H.
A 40,000-km² soft ground area in the southern Vietnam is big obstruction for infrastructure development in Vietnam. PVD is the most popular technique applied to improve soft ground in the southern Vietnam. However, field performance of PVD based on field monitoring is quite discrepant from prediction. This study aims at better understanding of PVD field performance via case studies. The two complete projects using PVD for soft ground improvement were utilized for back analysis. Field monitored settlements agree well with predicted settlement when the field settlement has experienced a settlements of 0.3 m or less. The predicted settlement exceeds the field monitored settlement about 50% when the field settlement reaches 0.5 m or larger. The result indicates that degree of filed consolidation was less than 90%, and large settlement keeps occuring during the service stage of highway embankments and may cause field settlement over the allowable settlement according to the Vietnam Code for sof ground improvement.
Keywords: Prefabricated vertical drain (PVD).; Consolidation; Highway embankment; Preload settlement; Soft ground; Wick drain